Sistem Pendukung Keputusan Pengadaan Alat Kesehatan Pada RS Indah Bagan Batu Dengan Menggunakan Metode Grey Absolute Decision Analysis (GADA) (Studi Kasus : RS Indah Bagan Batu) - Syaputra, Panca; Juledi, Angga Putra; Munthe, Ibnu Rasyid (MEANS (Media Informasi Analisa dan Sistem), 2023)
An medical devices are instruments, apparatus,machines or implants that do not containt drugs that are used to prevent, diagnose, cure and alleviate disease, or to shape the structure and improve body functions. The problem found by researchers is how to procure medical devices that have only relied on the intuition of the management team without being based on nalysis in meeting the needs of patients and hospitals. In this researcher, the write uses the method of Gray Absolute Decision Analysis (GADA) as a decision making solution to determie procurement of health equipment. This method is considered as the procurement of medical device because the dual method performs the drying process based on different attributes and weights and prioritizes and weights and prioritizes alternative data so that the results are more optimal and accurate in the procurement of medical devices.